The Difficulties of Effective English Speaking in Higher Secondary Level: An Empirical Study on City Area Colleges in Dhaka - Md. Ruhul Amin (Universitas Pendidikan Ganesha, 2023)
English has been inescapably used in everyday life in this period of intense global competition. But for various reasons, students in higher secondary level often struggle to develop adequate speaking skills. And these obstacles affect in their upcoming higher study, going abroad as well as in their future career. The study aims to analysing the prevailing barriers that the learners of higher secondary level encounter in speaking English effectively in their classrooms. This is a quantitative study and descriptive in nature. The respondents of this research were the higher secondary level learners selected by random sampling approach. Total 100 respondents were taken, 25 students from each school from three groups Science, Arts and Business Studies participated. The survey was conducted directly going to the respondents and the duration of the survey was one week. This study pinpoints all of these problems and presents possible recommendations for developing English competence. Future scholars will benefit from the insights of this study as they investigate the difficulties faced by English learners in Bangladesh.